Independensi Lembaga Perlindungan Data Pribadi di Indonesia - Nafisah, Sayyidah; Diniyanto, Ayon (Sharia Faculty, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The increase in cases of personal data breaches in Indonesia in recent years has become a very serious problem. So a personal data protection institution is needed to guarantee the protection of personal data. The existence of an independent personal data protection agency is an important aspect in carrying out personal data protection and is key in ensuring independence in the monitoring, auditing and prosecution processes. This is very crucial because regulations regarding personal data security apply to all public institutions, including executive, legislative and judicial. This research uses a normative juridical research type with a statutory approach, a comparative approach and a conceptual approach. The research results show that the personal data protection law that regulates this institution shows that there is executive involvement in the formation of the institution, thereby reducing its independence. As a result, this institution is at risk of being influenced by political interests and unable to carry out its duties accountably, effectively and efficiently.